Enhancing Antioxidant Potential via Fermentation of Red Violet Pigments Extracted from Red Spinach (Amaranthus tricolor) - SHAHRIN, PUTRI ELIA NATASHA; ABDULLAH, SHAKILA (Enhanced Knowledge in Sciences and Technology, 2024)
Amaranthus tricolor (A. tricolor), commonly known as red spinach, is a widely available and affordable leafy vegetable in Malaysia. It is rich in minerals, natural antioxidants, and bioactive compounds suitable for nutraceuticals which makes it an ideal source of natural food colouring. This research aims to develop a natural red food colouring alternative from red spinach that offers extra nutritional benefits in response to the growing concerns about synthetic food colourants. The research encompasses the extraction of red-violet pigments through maceration with acidified ethanol, followed by inoculating lactic acid bacteria (LAB) that were isolated from cultured milk for fermentation purposes using various parameters such as pH, temperature, carbon source concentration, and time until obtained the optimal fermentation for achieving the highest level of antioxidant activity. The optimized fermentation conditions include pH 6, 37°C, 0.5 g of glucose, and 7 days of fermentation, yielding the highest antioxidant activity. The fermented red spinach extract demonstrates superior DPPH and ABTS radical scavenging activity at 83.20% and 45.12% respectively compared to the unfermented extract. The total phenolic content for the fermented extract is 27.56 µg GAE/mL, while the unfermented extract is 17.62 µg GAE/mL. The fermented red spinach extract reveals a darker colour compared to the unfermented red spinach extract. No significant antimicrobial activity is observed against B. cereus and E. coli in both fermented and unfermented extracts. The findings contribute to the exploration of sustainable and health-promoting alternatives to synthetic food colourants in the food industry